Study of natural additives’ influence on the microbiological status of cereals - Grigorova, Svetlana; Pekov, Evgeni; Gjorgovska, Natasha (University Ss Ciril and Methodius in Skopje, Institute of Animal Science, 2019)
The antioxidant, antibacterial and antifungal effects of the natural plant additives such as turmeric powder, dry extract of geranium (Geranium sanguineum) and oregano oil on the contents of bacteria and moulds as well as the changes of pH and peroxide values in maize, wheat, barley and triticale during storage were studied. These additives have in a different extent, an inhibitory influence on the bacteria and moulds in the cereals chosen for the study, which depends on their composition and micro-organisms’ strain activity. Their influenceis directed mainly to the represent- atives of Aspergillus and Penicillinum species, whereas they have almost no influence on those of the genus Fusarium. Oregano oil achieved the highest antibacterial and antifungal effect. Turmeric powder showed a pronounced antifungal effect in wheat, barley and triticale. Geranium’s dry extract had a strong antibacterial effect, at the same time achieving only a weak antifungal effect. On 58th day and 136th day after the addition of these herbal additives, pH values were higher than those in untreated grains. The highest pH value was measured in the grains treated with oregano oil. All the pH values measured are within the normal range for maize and cereals, showing values between 5.41 and 6.44. Peroxide values obtained in the whole period of the trial don’t exceed 8 mEq O2/kg. These values are lower in the treated cultures than in the untreated ones.
Keywords: turmeric powder ; Geranium sanguineum ; oregano oil; cereals; mycolo gical status